Antibiotic resistance pattern and its correlation to the presence of tdh gene and CRISPR-Cas system in Vibrio parahaemolyticus strains isolated from seafood - Baliga, Pallavi; Shekar, Malathi; Ahamed, Shaik Tahur; Venugopal, M. N. (Indian Journal of Fisheries, 2019)
Vibrio parahaemolyticus is a pathogen native to the aquatic environment. In this study, 46 environmental V. parahaemolyticus isolates were subjected to a correlational analysis to find the association between their antimicrobial susceptibility pattern, prevalence of CRISPR-Cas system and thermostable direct hemolysin (tdh) gene. Antibiotic resistance profiling against eleven antibiotics revealed the isolates to be multidrug resistant. Isolates exhibited highest resistance to vancomycin (97.8%) followed by ampicillin (91.3%), cefotaxime (69.6%), ceftazidime/clavulanic acid (54.4%), ceftazidime (45.7%) and gentamicin (39.1%). CRISPR loci and tdh gene were detected in 47.83 and 58.7% of strains respectively. No significant correlation was observed between antibiotic resistance to presence of CRISPR, except in the case of gentamicin wherein, a negative correlation was seen (r=-0.272, p<0.10). Similarly, tdh did not correlate to antibiotic resistance. Seventeen strains in this study harboured the CRISPR loci as well as tdh gene, the association of which was found to be statistically significant. Keywords: Antimicrobial resistance, CRISPR, MAR index, Thermostable direct hemolysin (tdh), Vibrio parahaemolyticus